Experimental Study on The Relationship Between The Reflections From Surrounding Performers and Acoustic Properties - Yatani, Hitomi; Shimizu, Takafumi (MAJ - Malaysia Architectural Journal, 2025)
Concert halls, which are ubiquitous in cities, provide a venue for live music performances that are beloved by the public. However, the global pandemic of COVID-19 has led to restrictions on live music performances in concert halls. One such restriction requires performers on stage to maintain a certain distance from one another. This is because the droplets that are emitted by performers when performing musical instruments have been identified as a potential source of COVID-19 infection. To minimize the risk of infection, it has been recommended that wind instrument performers maintain a distance of at least 2 meters from one another, and that string instrument performers maintain a distance of 1.5 meters. However, adhering to these distances can make it challenging for performers to play their instruments. Previous studies have suggested that such challenges may affect the ability of performers to hear themselves and others on stage, but the specific causes of these difficulties have yet to be fully elucidated. The purpose of this study is to clarify the effects of different distances between performers on acoustic properties and auditory perception. Specifically, a sound field was created in an anechoic chamber using acoustic panels that simulated performers, and the impulse responses and acoustic properties were measured by varying the distance between these panels. In addition, subjective evaluation experiments were conducted using the measurement results. The study found that changes in the distance between performers affect not only auditory perception but also the acoustic properties of the sound field. These effects arise from reflections from surrounding performers at different distances and the absorption of sound by performers. The findings of this study will contribute to the creation of a more comfortable environment for performers.